2016
DOI: 10.1111/ans.13752
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of care in oesophago‐gastric cancer surgery in Australia

Abstract: Comparing a range of quality domains as a means of identifying areas of deficiency is feasible. This allows for contemporaneous improvements in service quality and may be more appropriate in the Australian setting than focusing on volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…Our cohort has a median age of 70 with a male predominance (54.8%). This is similar to age and gender ratio of gastric cancer cases nationally and when compared to recently published Australian series . Our overall resection rate was 44% which is slightly higher than the rate reported from Australia and the UK .…”
Section: Discussionsupporting
confidence: 90%
“…Our cohort has a median age of 70 with a male predominance (54.8%). This is similar to age and gender ratio of gastric cancer cases nationally and when compared to recently published Australian series . Our overall resection rate was 44% which is slightly higher than the rate reported from Australia and the UK .…”
Section: Discussionsupporting
confidence: 90%
“…However, in Australia, few high-volume hospitals report similarly high resection volumes, despite reporting mortality rates comparable with those of international 'high-volume' centres. 21 Thus far, Australian population-level studies of oesophagectomy 4,33 and pancreaticoduodenectomy, 19 which use high-volume thresholds similar to those in our study, have not reported significant mortality differences between hospitalvolume groups. This may relate to a lack of statistical power in these studies due to lower numbers of resections and a shorter time-period of assessment as compared with our study, low rates of postoperative mortality following these procedures reported in Australia 22 and the presence, in some low-volume centres, of hospital characteristics including high hospital technology, high-level intensive care, interventional-radiology services, and surgical training programmes which have been reported to be associated with improved post-operative mortality following upper gastrointestinal cancer surgery, independent of hospital-volume.…”
Section: Discussionsupporting
confidence: 57%
“…[15][16][17][18] By comparison, population-level studies in Australia have not reported improved post-operative mortality with higher hospital-volume following pancreaticoduodenectomy, 19 while for oesophagectomy, reports of improved mortality with higher surgical volumes are conflicting. 3,4,20 This may relate to lower resection volumes in Australian centres, including those considered 'high-volume', when compared with the volumes reported by centres in other countries, [10][11][12][13][14]19,21 and to the generally low mortality rates reported by Australian centres performing these procedures. 22 As well, some low-volume centres in Australia offer services including specialist surgeons, advanced endoscopy and interventional-radiology services which have been reported to be associated with lower postoperative mortality following complex upper gastrointestinal procedures such as pancreatic resection, independent of hospital resection volume.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, gastric cancer was estimated to account for over 700 000 deaths globally and over 1000 deaths in Australia . Surgical resection is the only curative treatment with 30‐day post‐operative mortality rates in western populations reported to be 1.6–16% …”
Section: Introductionmentioning
confidence: 99%
“…These services are reported to be associated with improved post‐operative mortality following other complex upper gastrointestinal surgery, such as pancreatic resection . A high hospital service capability, with appropriately trained surgeons, may explain why some Australian low‐volume centres report post‐operative mortality outcomes equivalent to those reported by centres with much higher resection volumes …”
Section: Introductionmentioning
confidence: 99%